The Effectiveness of Blended Learning in Improving Media Literacy on Different Self-Regulated Learning - Muhammad Rais; Ratnawati Fadillah; Andi Alamsyah Rivai (Journal of Educational Science and Technology (EST), 2019)
The purpose of this study was to examine the effectiveness of learning strategies of blended and self-regulated learning and the effect of the interaction between them on media literacy skills. This study used a quasi-experimental design with a 2x2 factorial design. The research subjects consisted of 85 people (41 in control groups and 44 in experimental groups). Data were analyzed using two-way ANOVA. The results showed that (1) there were differences in media literacy abilities between groups of students who were taught using blended learning strategies and groups of students who were taught using face to face learning strategies (F = 26,034; p = 0,000), (2) there were differences in media literacy abilities between groups of students who have high self-regulated learning and low self-regulated learning, (F = 7,446; p = 0.008), and (3) there was no interaction between learning methods and self-regulated learning (high and low) on literacy skills Student media (F = 0.238; p = 0.627). Descriptive statistical results indicated that the use of blended learning strategies has a better effect with an average score of 37.66 compared to face-to-face learning strategies that have a relatively smaller average score of 34.02.